Between Conflict and Harmony: Understanding Contestation of Iftirāq Al-Ummah Hadiths in the Contemporary Era - Muna, Arif Chasanul (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
Iftirāq al-ummah hadith in the contemporary era is considered a problematic hadith both at the level of understanding and practice. The meaning of the hadith is considered to be contrary to the Qur'an and other hadiths which uphold the spirit of unity and brotherhood. At the practical level, this hadith is considered to be a trigger for division and conflict among Muslims. This study aims to map contemporary scholars' understanding models of iftirāq al-ummah hadith. To track this understanding model, the main questions are: 1) what is the model for the tendency of contemporary scholars to understand the hadith, 2) what is the impact of each model of understanding on the scientific world of hadith and also the praxis of people's lives, and 3) how to construct arguments built. This research is a narrative-historical approach, as well as content analysis that combines descriptive, critical and hermeneutical analysis, this study shows that the understanding of contemporary scholars of the iftirāq al-ummah hadith can be grouped into three models, namely 1) exclusive understanding model; 2) rejective understanding model; 3) inclusive understanding model; 4) introspective understanding model. The first understanding tends to cause conflict among Muslims, while the other three are criticisms of the first model. Each understanding put forward coherent arguments and pragmatic arguments to strengthen his opinion.